Preventing Radicalism through Integrative Curriculum at Higher Education - Saca Suhendi; Wagdy Abdel-Fatah Sawahel; Kafil Yamin Abdillah (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2020)
Religious radicalism which spread across the globe has turned into a global problem and raised concern among scholars to discuss. Higher education institutions which are supposed to educate cadre of high-intensity scholars on an empirical level have to some extent failed to meet the expectation. In Indonesia, some of the institutions have been deemed as a place of metamorphosis for potential site to nurture radicalism understanding and movement among their students on campus. This paper was aimed at investigating university effort to join the global struggle against radicalism. This study applied descriptive qualitative research using survey methods. Data were collected using observation and documentation. Using the theory of positive radicalism which demands transformation with a comprehensive religious understanding, this study analyzed the data. The results of the study show that the phenomenon of radicalism at higher education can be handled by implementing integrative curriculums as one of the feasible ways for higher education institutions to participate and establish their role. Integrative curriculum can be applied to catalyze new energy to present a more comprehensive and tolerant atmosphere by emphasizing the role of Islam in building world civilization.